230 days of ultra long‐term subcutaneous EEG: seizure cycle analysis and comparison to patient diary. Issue 1 (4th December 2020) - Viana, Pedro F.; Duun‐Henriksen, Jonas; Glasstëter, Martin; Dümpelmann, Matthias; Nurse, Ewan S.; Martins, Isabel P.; Dumanis, Sonya B.; Schulze‐Bonhage, Andreas; Freestone, Dean R.; Brinkmann, Benjamin H.; Richardson, Mark P.
Abstract: We describe the longest period of subcutaneous EEG (sqEEG) monitoring to date, in a 35‐year‐old female with refractory epilepsy. Over 230 days, 4791/5520 h of sqEEG were recorded (86%, mean 20.8 [IQR 3.9] hours/day). Using an electronic diary, the patient reported 22 seizures, while automatically‐assisted visual sqEEG review detected 32 seizures. There was substantial agreement between days of reported and recorded seizures (Cohen's kappa 0.664), although multiple clustered seizures remained undocumented. Circular statistics identified significant sqEEG seizure cycles at circadian (24‐hour) and multidien (5‐day) timescales. Electrographic seizure monitoring and analysis of long‐term seizure cycles are possible with this neurophysiological tool.